OTORISASI BAGI ALUMNI DALAM MENINGKATKAN KEPERCAYAAN MASYARAKAT: Studi Kasus pada KBIHU Nurul Haramain Kabupaten Probolinggo - Moh Rifa'i; Ahmad Tijani; Zubairi Zubairi (Jurnal Asy-Syukriyyah, 2022)
The embodiment of public trust cannot be carried out by all pilgrimage guidance groups, in order to attract people's hearts. This effort requires perfect service and cooperation with alumni of the pilgrims. KBIHU Nurul Haramain has congregations that increase in volume from year to year. Done by good service in reliability system, professional management, and other capabilities. This research was conducted using a qualitative method, with a descriptive type, and the data was taken directly from KBIHU Nurul Haramain through direct interviews, observation and documentation. While the data analysis is by collecting all the data, reducing the data and concluding the data, the validity of the data uses the triangulation model (researchers, data sources, methods and theories). This research uses Sunarno's theory about alumni involvement in an institution. The results of research in this journal are to form a forum for alumni reunion of pilgrims, create good relations with alumni of pilgrims, collaborate with alumni, and create quality alumni, so as to increase public trust.